Analisis Pengaruh Biaya Overhead,Biaya Risiko,Volume Pembiayaan Murabahah Dan Posisi Likuiditas Terhadap Pendapatan Margin Murabahah Pada PT. Bank Central Asia Syariah, Tbk. Periode 2012-2020 - Anisya Fitriyah; Dedi Suselo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to analyze the effect of Overhead Costs, Risk Costs, Volume of Murabahah Financing and Liquidity Positions on Murabahah Margin Income. The method used is the quantitative method using secondary data. The data used in this study are the financial statements of PT Bank BCA Syariah for the period 2012-2020. The statistical test used is the classical assumption test and multiple linear regression analysis. The results obtained from the data analysis are a correlation coefficient of 0.781. This shows a positive correlation between Overhead Costs, Risk Costs, Murabahah Financing and Liquidity Positions on Murabahah Margin Income at PT Bank BCA Syariah, Tbk. The hypothesis shows an effect of Overhead Cost, Risk Cost, Murabahah Financing Volume and Liquidity Position on Murabahah Margin Income at PT Bank BCA Syariah, Tbk, which is 75.3%. This study provides empirical evidence that Overhead Costs, Risk Costs, Murabahah Financing Volume and Liquidity Position (Cash Ratio) have a significant effect on Murabahah Margin income at PT Bank BCA Syariah, Tbk.